Situations in which mothers experience difficulty stimulating healthy EBRB in school-aged children. (13th November 2019) - Ruiter, E L M; Fransen, G A J; Molleman, G R M; Hoeijmakers, M J H M; van der Velden, K; Engels, R C M E
Abstract: Background: Parental support is an important element in overweight prevention programs for children. The purpose of this study was to examine everyday life situations in which mothers encounter difficulties encouraging healthy energy balance-related behavior in their school-age children. Methods: We formed four focus groups containing 6-9 participants each. The participants were mothers of Dutch, Turkish, or Moroccan descent with a child 8-13 years of age. All focus group sessions were recorded, transcribed, and coded. Content was analyzed conventionally using ATLAS.ti 6. Results: Twenty-seven difficult everyday life situations were identified in 14 settings. The five most frequently reported situations were a daily struggle regarding eating vegetables, eating breakfast on time before going to school, eating candy and snacks between meals, and spending excessive time watching television and using the computer. A perceived loss of parental control, the inability to establish rules and the failure to consistently enforce those rules were the most commonly cited reasons for why the mothers experience these situations as being difficult. Conclusions: We identified five difficult everyday life situations related to healthy energy balance-related behavior. These five difficult situations were used as the input for developing a web-based parenting program designed to prevent children from becoming overweight. We reasoned that if we use these situations and the underlying reasons, many parents would recognize these situations and are willing to learn how to deal with them and complete the e-learning. Key messages: The identified everyday-life-situations in which mothers experience difficulty stimulating healthy EBRBs in their children age 8-13 were used as input for our e-learning program to prevent overweight. Mothers who live in low-SES neighborhoods were easily willing to participate in focus groups and discuss EBRB-related topics.